Urbanization and Women Empowerment: Evidence from India - Gaurav Dhamija; Punarjit Roychowdhury; Binay Shankar (Global Labor Organization (GLO), 2023)
The paper examines the short-term implications of urbanization on women empowerment in India. In theory, urbanization can affect women either positively or negatively. Women in urban areas, compared to their rural counterparts, are thought to enjoy greater social, economic, and political opportunities and freedoms. At the same time, research shows barriers to women's empowerment remain widespread in urban environments. We measure urbanization using satellite-based nighttime light intensity data. Fixed effects estimation results show that urbanization positively affects women's labor market participation, agency within households, mobility, access to information, and attitudes toward domestic violence (thereby making them more likely to report incidences of violence). However, the effect of urbanization on women's financial autonomy is negative, and on health is mixed. These results, we show, are robust to unmeasured confounders to a large extent. In light of the rapid urbanization that India is currently experiencing, the importance of these findings cannot be overemphasized. They suggest that while urbanization could go a long way toward economically empowering women in India, the government also needs to devise complementary policies and interventions that could tackle the adverse consequences of urban expansion.
Keywords: J16; O12; 330; Gender; India; Nighttime Lights; Urbanization; Women Empowerment